Holocene environmental changes recorded by magnetic parameters of sediments in the Yangtze River Delta and implications for prehistoric cultural development - Guiye Zhang; Longsheng Wang; Shouyun Hu; Mingming Ma; Jiawen Zhao; Yanjun Ge; Lin Zeng; Xianbin Liu (Estuarine, Coastal and Shelf Science, 2026)

Corrigendum to “Alterations in the amino acid profile of follicular fluid of cows following ovarian stimulation and its association with oocyte quality and embryonic development” [Theriogenology 2026; 118017] - Yao Li; Jie Wang; Jiajing Liang; Ning Yang; Yupeng Xu; Baoli Zhao; Mingming Liu; Xingxing Ling; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin; et al. (Theriogenology, 2026)

Alterations in the amino acid profile of follicular fluid of cows following ovarian stimulation and its association with oocyte quality and embryonic development - Yao Li; Jie Wang; Jiajing Liang; Ning Yang; Yupeng Xu; Baoli Zhao; Mingming Liu; Xingxing Ling; Pengfei Lin; Huatao Chen; Aihua Wang; Yaping Jin; et al. (Theriogenology, 2026)

Projections of heatwave-attributable preterm births in China (2025-2100): The effects of climate scenarios and adaptation measures - Mingming Pan; Xuen Nie; Guangtao Fan; Yufeng Miao; Zhuohui Zhao; Zhiwen Luo; Shao Lin; Qihong Deng (Sustainable Cities and Society, 2026)

Multi-level biomarker responses in Eisenia fetida co-exposed to PE-MPs and DiBP: An ecological risk assessment based on physiological, biochemical, and molecular indicators - Yanan Zhang; Yumu Luo; Zhensi Meng; Jun Luo; Ke Li; Yuhang Lin; Minle Li; Rongren Bin; Mingming Fu; Ming Hung Wong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Shifting baseline syndrome and the transformation of ecological knowledge among Chinese marine fishers - Yifei Cai; Mingli Lin; Yuanyuan Li; Agathe Serres; Mingming Liu; Lijun Dong; Haozhong Chen; Zirui You; Songhai Li (Biological Conservation, 2026)

Monitoring urban carbon dioxide emissions from the atmosphere: insights from vertical tower observations in Beijing, China - Kewei Liu; Wudi Cao; Mingming Zhu; Zifa Wang; Fei Hu; Lin Wu; Xueling Cheng (Atmospheric Environment, 2026)

Social Arousal and Interspecific Calf Handling by Short‐finned Pilot Whales - Agathe Serres; Mingming Liu; Mingli Lin; Hongri Wang; Xiuqing Hao; Songhai Li (Marine Mammal Science, 2026)

Targeting Peroxiredoxin 6: Tannic Acid Inhibits Singapore Grouper Iridovirus Infection via PRDX6‐Dependent Pathway and Antioxidant Response - Xiangmou Qin; Chen‐Ao Li; Lin Huang; Qing Yu; Mingming Zhao; Yanxia Gao; Jiaxi Li; Jia Cai; Huapu Chen; Fei Ling; Junxiang Lai; Ermeng Yu; et al. (Journal of Fish Diseases, 2026)
Singapore grouper iridovirus (SGIV) is a major viral pathogen threatening grouper aquaculture. The lack of specific antiviral drugs underscores the urgent need to develop safe and effective control strategies. This study demonstrates that tannic acid (TA) exhibits significant anti‐SGIV activity in vitro. In grouper spleen (GS) cells, TA inhibited SGIV replication in a concentration‐dependent manner. Time‐of‐addition assays confirmed its antiviral efficacy when applied either before or after SGIV infection. Mechanistically, TA directly interfered with SGIV particle infectivity, viral adsorption, entry and intracellular replication. Network pharmacology analysis suggested TA's targets are associated with host cellular antioxidant pathways, among which Peroxiredoxin 6 (PRDX6) was identified as a potential target of TA. Further experiments confirmed that TA upregulated the Nrf2 antioxidant pathway and suppressed the expression of pro‐inflammatory cytokines (IL‐1β, IL‐8). Notably, TA enhanced the expression of PRDX6, and overexpression of PRDX6 significantly inhibited SGIV replication, indicating that PRDX6 contributes to the antiviral effect of TA. In vivo, TA treatment not only restored PRDX6 expression in infected groupers but also significantly reduced viral load in liver and spleen following SGIV infection. These findings demonstrate that TA inhibits SGIV through direct viral interference and PRDX6‐mediated antioxidant modulation, highlighting its potential as a natural therapeutic agent against SGIV.

Precision design of hydrogel polymer nanoparticles: How side-chain spatial arrangement and length matching govern antibacterial activity, physiological robustness, and selectivity - Weixiang Zhang; Weicheng Tang; Bo Li; Shiqi Lin; Mu Yuan; Lei Su; Wenfeng Tan; Gailing Yuan; Mingming Liu (Chemical Engineering Journal, 2026)

Efficient removal of atrazine by phosphorylated nano zero-valent iron activated persulfate process: Performance, reaction mechanism and degradation pathway - Jun Lin; Menghua Cao; Guohong Qiu; Hengliang Huang; Tianying Wan; Shuxin Tu; Shuanglian Xiong; Mingming Zheng (Process Safety and Environmental Protection, 2026)

Fracture evolution and mechanical response of coal with damage induced by oil-gas seepage - Yawu Shao; Wei Yao; Lei Zhu; Gang Han; Haifei Lin; Hu Liu; Jiahao Xie; Mingming Sun; Jin Wang (Bulletin of Engineering Geology and the Environment, 2026)

Epigallocatechin Gallate (EGCG) Inhibits Singapore Grouper Iridovirus (SGIV) Infection by Interfering With Viral Life Cycle and Modulating Host Cell Cycle G2/M Checkpoint - Tianhong Zhao; Jinkun Xie; Chen‐Ao Li; Mingzhu Liu; Qing Yu; Lin Huang; Yanxia Gao; Mingming Zhao; Jiaxi Li; Jia Cai; Huapu Chen; Fei Ling; et al. (Journal of Fish Diseases, 2026)
Singapore grouper iridovirus (SGIV) is a highly pathogenic virus that causes substantial economic losses in marine grouper aquaculture, and effective antiviral agents are currently lacking. In this study, the anti‐SGIV activity of epigallocatechin gallate (EGCG), a natural compound from green tea, was evaluated and its underlying mechanisms were investigated. Cytotoxicity assays showed that EGCG at concentrations up to 12.5 μg/mL was safe for grouper spleen (GS) cells. EGCG treatment reduced viral MCP and VP19 mRNA expression in a dose‐dependent manner, indicating its anti‐SGIV activity. Mechanistic studies revealed that EGCG directly impaired SGIV particle infectivity and interfered with viral adsorption, entry, and intracellular replication. Network pharmacology analysis identified overlapping genes between EGCG targets and SGIV‐induced differentially expressed genes, with enrichment pathways related to cell cycle regulation, particularly the G2/M checkpoint. Further studies showed that SGIV infection upregulated the G2/M checkpoint regulators WEE1 and CHEK2, and EGCG treatment reversed these dysregulations, suggesting that EGCG alleviates SGIV‐induced G2/M arrest. In vivo, EGCG treatment significantly reduced viral load in infected groupers and improved survival rate. Collectively, these findings demonstrate that EGCG exerts potent anti‐SGIV activity both in vitro and in vivo by directly targeting multiple steps of the viral life cycle and modulating host cell cycle G2/M checkpoint pathways, highlighting its potential as a natural therapeutic agent against SGIV infection.

Virus-host metabolic interaction: SGIV-induced protein lactylation suppresses viral propagation - Mingming Zhao; Jiaxi Li; Mingzhu Liu; Ying Pan; Sining Su; Xiangmou Qin; Yanxia Gao; Lin Huang; Junxiang Lai; Jia Cai; Huapu Chen; Qing Yu; et al. (Fish & Shellfish Immunology, 2026)

Mutual activation of g-C3N4 and persulfate synchronizes rapid visible-light-triggered fabrication of multifunctional hydrogels - Mingming Deng; Dagang Zhou; Lin Luo; Boyi Fu; Ping Li; Qi Liu; Chi Huang (Chemical Engineering Journal, 2026)

Optimization of pediatric dosing regimens for aztreonam and amoxicillin/clavulanate combination therapy against multidrug-resistant bacteria - Lili Wang; Mengyuan Wu; Lin Qu; Pengfei Wang; Ziwei Yu; Hua Deng; Frederico S. Martins; Jiayuan Zhang; Da Rong; Mingming Yu; Zhihua Lv; Sherwin K. B. Sy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Ectomycorrhizal and saprotrophic fungi are linked to reduced pathogenic fungi across roots and rhizosphere soils of major afforestation species in northeastern China - Wen Guo; Xiangxia Yang; Yaping Liu; Xiaoding Lin; Le Chang; Yaru Wei; Mingming Xia; Minghao Lv; Kazuo Isobe (Soil Ecology Letters, 2026)

Atmospheric Boundary Layer Eco-Environment Shanghuang Observatory: An Integrated Multiscale Research Platform in Southeastern China for Understanding Boundary Layer Processes, Atmospheric Chemistry Feedback, and Extreme Weather–Climate Linkages - Zifa Wang; Xiaole Pan; Yele Sun; Jinyuan Xin; Hang Su; Junji Cao; Jie Li; Ting Yang; Hang Liu; Weijie Yao; Weiqi Xu; Xueshun Chen; et al. (Advances in Atmospheric Sciences, 2026)

Advances and Perspectives in Atmospheric Environment Modeling in China - Zifa Wang; Xinwei Li; Meng Gao; Baozhu Ge; Xiao Tang; Xueshun Chen; Qizhong Wu; Lin Wu; Zhe Wang; Ting Yang; Xiaole Pan; Huansheng Chen; et al. (Advances in Atmospheric Sciences, 2026)

Permeability Evolution and Failure Behavior of Coal Under Coupled Oil–Gas Porous Flow and Mining-Induced Stress - Yawu Shao; Lei Zhu; Gang Han; Haifei Lin; Wei Yao; Hu Liu; Jiahao Xie; Tao You; Mingming Sun; Jin Wang (Rock Mechanics and Rock Engineering, 2026)

Hydraulic optimization of a V-weir-orifice composite fishway with column structures of different shapes for estuarine connectivity restoration - Chunying Shen; Jinghan Lin; Mingming Wang; Yubin Chen; You Wang; Jing Sun (Ocean Engineering, 2026)

Increased Soil Carbon and Nitrogen Stocks Associate With Stronger Calcium–Microbial and Multi‐Trophic Interactions Under Warming - Dan Xiao; Wei Zhang; David R. Johnson; Peilei Hu; Lin Xu; Mingming Sun; Li Tang; Xunyang He; Jie Zhao; Xionghui Liao; Wanxia Peng; Hongsong Chen; et al. (Global Change Biology, 2026)
Converting cropland to planted forests improves soil organic carbon (SOC) and total nitrogen (TN) storage while contributing to climate change mitigation, primarily through the regulation of belowground organisms and mineral protection such as calcium (Ca). However, the mechanistic pathways linking exchangeable Ca 2+ , soil micro‐food web interactions, and nutrient accumulation under warming remain unclear. Here, we investigated their potential roles in driving the accumulation of mineral‐associated organic matter (MAOM), SOC, and TN in planted forests compared with croplands under warming conditions. Planted forests exhibited higher MAOM, SOC, and TN than cropland and had stronger coupling between carbon and nitrogen. Warming increased MAOM, SOC, and TN in planted forests but reduced SOC in cropland. Compared to cropland, planted forests displayed elevated levels of soil exchangeable Ca 2+ , microbial necromass carbon and nitrogen, stronger Ca–microbial and multi‐trophic associations. Warming further amplified positive Ca–microbial (e.g., bacteria and fungi) and cross‐trophic associations (e.g., nematode–bacteria, nematode–fungi, nematode–protist, and omnivore‐predator–bacteria/fungi) in planted forests by increasing plant productivity, litter biomass, and soil exchangeable Ca 2+ , whereas cropland showed limited responsiveness to temperature changes. In planted forests, soil exchangeable Ca 2+ was positively correlated with Ca–microbial and cross‐trophic associations, microbial necromass carbon and nitrogen, and the contents of MAOM, SOC, and TN. These relationships were absent in cropland. Notably, cross‐trophic associations rather than microbial abundance or diversity, with significant modulation by soil exchangeable Ca 2+ , had the strongest positive relationship with MAOM, SOC, and TN accumulation in planted forests. Collectively, our findings lead to the hypothesis that warming promotes SOC and TN storage in planted forests by jointly strengthening exchangeable Ca 2+ , Ca–microbial and cross‐trophic interactions. These results highlight the potential importance of multi‐trophic interactions and Ca‐mediated processes in stabilizing microbial necromass and fostering carbon and nitrogen preservation during vegetation restoration in response to warming.

Size-dependent effects of polystyrene Nanoplastics on hepatic Immunometabolism and the gut-liver Axis in the Swamp Eel (Monopterus albus) - Mingming Han; Wenzong Zhou; Ji Liang; Aileen Tan Shau-Hwai; Zihan Zhou; Lin Cheng; Jiayuan Liao; Weiwei Huang; Qichen Jiang; Weiwei Lv (Aquaculture, 2026)

Coral-inspired in situ immobilized lipase on covalent organic framework for efficient synthesis of flavor esters - Shengli Ding; Mengqi Wang; Guiqing Lin; Yanrong Song; Ji Zhang; Yufei Zhang; Mingming Zheng (Food Chemistry, 2026)

Synergistic effects of multi-frequency ultrasonication on starch-gum interactions for sialorrhea management: Implications for structural, functional, digestibility properties, and molecular docking studies - Muhammad Awais; Wenjiang Dong; Baoguo Xu; Qiufang Liang; Lin Xiangyu; Yufan Sun; Mingming Zhong; Mohamed Ibrahim Younis; Husnain Raza; Ekram Abd El-Salam; Xiaofeng Ren (Food Hydrocolloids, 2026)

A liquid reactive flame retardant strategy for CF/EP composites fabricated by vacuum infusion process - Mingming Yu; Jiaying Yao; Jiaxin Ma; Zhimin Gao; Dong Feng; Hao Huang; Ousheng Zhang; Wen Ye; Wang Xie; Lin Fang; Musu Ren; Jinliang Sun (Chemical Engineering Journal, 2026)

Bio-based vitrimer with superior rigidity-flexibility balance and high reprocessability fabricated via dynamic crosslinking and stepwise hot-pressing strategy - Mingming Yu; Rongbin Xiao; Xiaolei Wang; Haigang Xiao; Lin Fang; Wang Xie; Musu Ren; Jinliang Sun (Chemical Engineering Journal, 2026)

Hybridizing deep learning models and a chemical transport model for medium-term PM2.5 forecasts in the Yangtze River Delta, China - Mingming Zhu; Lin Wu; Qi Liao; Zixi Wang; Wudi Cao; Si Zhang; Xiaole Pan; Jie Li; Jinyuan Xin; Yele Sun; Jiang Zhu; Zifa Wang (Journal of Environmental Sciences, 2026)

Diverse Mixed‐Species Cetacean Groups in the South China Sea: First Documentation From a Potential Important Marine Mammal Area - Mingming Liu; Mingyue Ouyang; Wenzhi Lin; Lijun Dong; Agathe Serres; Mingli Lin; Songhai Li (Marine Mammal Science, 2026)

Galla Chinensis as an antiviral agent: Targeting Micropterus salmoides rhabdovirus infection - Jieying Yu; Mingzhu Liu; Qing Yu; Xiangmou Qin; Mingming Zhao; Ying Pan; Nijia Xue; Hao Wang; Songlin Li; Fei Ling; Gaoxue Wang; Shuyu Han; et al. (Fish & Shellfish Immunology, 2025)

Unlocking biochar's carbonyl group: Fe-Mn oxide synergy enables high-efficiency As(III) immobilization via non-radical oxidation - Zihang Cheng; Yilin Wu; Ruiqi Du; Mingming Lin; Jingzi Beiyuan; Juan Liu; Peng Liu; Bowen Li; Xueding Jiang; Hailong Wang (Journal of Environmental Management, 2025)

Mechanistic insights into H2O2 activation by high-density iron single-atom catalysts for efficient water treatment: Surface-bound radical and singlet oxygen - Fuhang Xu; Cui Lai; Mingming Zhang; Zuying Yao; Dengsheng Ma; Bisheng Li; Meng Qin; Huchuan Yan; Xiuqin Huo; Xing Fan; Biting Wang; Shiyu Liu; et al. (Journal of Environmental Chemical Engineering, 2025)

Oxygen vacancy-assisted CuCo tandem catalyst boosts efficient electrocatalytic neutral ultralow-concentration nitrate to ammonia - Xing Fan; Cui Lai; Lei Qin; Mingming Zhang; Huchuan Yan; Shiyu Liu; Dengsheng Ma; Qianting Liu; Lin Tang (Chemical Engineering Journal, 2025)

Distribution pattern of cetaceans in the northern South China Sea based on visual surveys and environmental DNA metabarcoding - Shengming Deng; Xiang Zhang; Min Liu; Bai‐An Lin; Yongcan Zhou; Mingming Liu; Wenzhi Lin; Mingli Lin; Lijun Dong; Hui Kang; Binshuai Liu; Shenglan Chen; et al. (Conservation Biology, 2025)
The South China Sea (SCS) is vital habitat and potential nursery and feeding grounds for large cetaceans, such as the sperm whale ( Physeter macrocephalus ), making understanding of the temporal and spatial patterns of cetaceans in this region essential. We examined the accuracy of environmental DNA (eDNA) in detecting cetacean species diversity and determine the spatial and temporal distribution of cetaceans in the northern SCS. We conducted 5 ship‐based visual surveys for cetaceans in 3 summers and 2 springs from 2020 to 2023 and used eDNA metabarcoding to determine the relative abundance and spatial and temporal distribution of cetaceans in offshore and abyssal areas of the northern SCS. We detected 18 cetacean species through visual observations and eDNA metabarcoding. Both methods identified 12 species in common. Cetaceans’ presence varied temporally. We detected 7 species in the springs and 17 species in the summers. Expedition route design, meteorological conditions, and sea conditions between the 2 seasons partly explained the seasonal differences. The species of Ziphiidae, Physeteridae, and Kogiidae tended to occupy regions with high bathymetric drop gradients, particularly those situated on continental slopes and seamounts. The Delphinidae were more widely distributed and relatively more abundant. Of the cetaceans successfully identified by eDNA metabarcoding, species with relatively large group sizes and that were relatively close to the sampling sites tended to be more easily detected. Our results provide new information on the relative abundance and spatial and temporal distribution of cetaceans and indicate that eDNA techniques can provide additional information and serve as a complementary tool for cetacean monitoring and conservation.

Magnetic characteristics of sediments in the northern Yangtze River delta since MIS3 and their responses to palaeoenvironmental changes - Guiye Zhang; Longsheng Wang; Xiaohui Wang; Shouyun Hu; Mingming Ma; Jiawen Zhao; Yanjun Ge; Lin Zeng; Xianbin Liu; Chao Zhan; Qing Wang (CATENA, 2025)

A rich carbohydrate-lipid kitchen waste upcycling via Chlorella vulgaris cell proliferation and biomass production strategy - Ting Zhang; Hao Zhou; Mingming Zhao; Dingqiang Zhang; Lin He (Bioresource Technology Reports, 2025)

Investigating the structure of a multiple karst aquifer system and its hydrological process response using high-resolution multi-tracer data - Huaisong Ji; Gabriele Chiogna; Wei Chang; Beatrice Richieri; Lin Chen; Mingming Luo; Xulei Guo; Kun Huang (Journal of Hydrology, 2025)

Initiatorless solar-photopolymerized heterostructured hydrogel with high performance, environmental adaptability, and recyclability - Chenghao Wang; Ping Li; Mingming Deng; Lin Luo; Boyi Fu; Qi Liu; Chi Huang (Chemical Engineering Journal, 2025)

Suppression of TaHDA8-mediated lysine deacetylation of TaAREB3 acts as a drought-adaptive mechanism in wheat root development - Zehui Liu; Qun Yang; Xingbei Liu; Jinpeng Li; Lei Zhang; Wei Chu; Jingchen Lin; Debiao Liu; Danyang Zhao; Xiao Peng; Chaowu Zeng; Mingming Xin; et al. (Molecular Plant, 2025)

Forest or grassland? A quantitative analysis of urban residents' green exposure preference by using multi-temporal mobile signal data - Hongkai Geng; Tao Lin; P.M. van Bodegom; Mingming Hu; Yicheng Zheng; Zixu Jia; Junmao Zhang; Xiangzhong Guo; Yuan Chen; Meixia Lin; Jiayu Cai; Jing Lin (Urban Forestry & Urban Greening, 2025)

Nb-modified ZSM-48 as efficient catalysts for hexadecane hydroisomerization - Pengju Wei; Wei Wang; Yujing Chen; Mingming Zhang; Xuerong Zhou; Xiaozhen Chen; Qingquan Lin; Kaixuan Yang; Miao Zhang (Fuel, 2025)

Konjac glucomannan/xanthan gum film embedding soy protein isolate–tannic acid–iron complexes for blueberry preservation - Zhenzhen Wu; Lin Wang; Chen Ma; Mingming Xu; Xiuqing Guan; Fen Lin; Tengjun Jiang; Xianrui Chen; Nitong Bu; Jie Duan; Wei Liu; Jie Pang (Food Hydrocolloids, 2025)

The OLR1/NF-κB feedback loop exacerbates HIV-1 Tat-induced microglial inflammatory response and neuronal apoptosis - Qifei Zhang; Wenhua Tao; Jing Wang; Meijuan Qian; Mingming Zhou; Lin Gao (Journal of NeuroVirology, 2025)

Effects of extreme precipitation on soil erosion affected by typhoons in central Shandong Province, China - Mingming Dong; Yousheng Wang; Jing Guo; Lin Meng; Zhen Xu; Zhikai Liu; Bing Liu; Lei Zhang; Bing Yin (Journal of Soils and Sediments, 2025)

National scale sub-meter mangrove mapping using an augmented border training sample method - Jinyan Tian; Le Wang; Chunyuan Diao; Yameng Zhang; Mingming Jia; Lin Zhu; Meng Xu; Xiaojuan Li; Huili Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

A simple and colorimetric method utilizing cell-free toehold switch sensors for the detection of Chlamydia trachomatis, Ureaplasma urealyticum and Neisseria gonorrhoeae - Fengling Fang; Hongyan Guo; Zhaopei Guo; Lin Lin; Lu Lai; Yue Shi; Weiquan You; Shanjian Chen; Can Liu; Mingming Zhao; Shaobin Guo; Qishui Ou; et al. (Analytica Chimica Acta, 2025)

Dietary supplementation of Roseovarius litoreus improves survival and immune defense of the swimming crab Portunus trituberculatus - Mingming Niu; Weichuan Lin; Qingyang Wu; Ce Shi; Changkao Mu; Chunlin Wang; Yangfang Ye (Aquaculture, 2025)

Long-lasting social bonds of a habitat-structured delphinid social system - Shenglan Chen; Wenzhi Lin; Binshuai Liu; Agathe Serres; Mingli Lin; Mingming Liu; Songhai Li (Animal Behaviour, 2025)

Solar interfacial evaporation hydrogel with distributed packaging of phase change materials for continuous desalination - Qian Chen; He Zhang; Lie Zou; Rui Yang; Guangyong Zeng; Pengcheng Lin; Liu Yang; Mingming Zheng; Xiaoke Li (Chemical Engineering Journal, 2025)

Study on frost deformation of rock and calculation method of frost heaving rate of tunnel surrounding rock in cold regions - Wenliang Qiu; Fengqi Shen; Jingyu Zhou; Lin Qi; Mingming Xing (Earth Science Informatics, 2025)

The first genetically confirmed live sighting of the Deraniyagala's beaked whale ( Mesoplodon hotaula ), with insights into the diversity, phylogeny, and past demographic history - Wenzhi Lin; Hui Kang; Inge Seim; Binshuai Liu; Shenglan Chen; Mingming Liu; Lijun Dong; Mingli Lin; Yuhang Song; Mingyue Ouyang; Xiaoyu Huang; Yingxue Gao; et al. (Marine Mammal Science, 2025)
Beaked whales have recently been reported in the South China Sea but with taxonomic uncertainty due to their ambiguous morphological features. Here, we sequenced three genetic markers, the control region (CR) and cytochrome b ( cytb ) of the mitochondrial genome and the first intron of the nuclear muscle actin gene ACTA2 , of two biopsy samples collected in 2021, and revealed unambiguous clustering with sequences previously attributed to Deraniyagala's beaked whale ( Mesoplodon hotaula ). Phylogenetic analysis of complete mitogenomes strongly supported the close relationship between the Deraniyagala's beaked whale and the ginkgo‐toothed beaked whale ( M. ginkgodens ). Whole‐genome sequencing suggested a high degree of heterozygosity in the Deraniyagala's beaked whale. Ancient inbreeding may have had a greater impact than the recent inbreeding on Deraniyagala's beaked whales, but more samples are needed to draw a firm conclusion. The approximate effective population size of Deraniyagala's beaked whale was found lowest among seven examined ziphiids, which has been experiencing a steady decline since ~300,000 ya. Therefore, we suggest that the conservation status of Deraniyagala's beaked whales should be assessed when essential information is available. The results of our study provide genetic evidence of the live sighting of Deraniyagala's beaked whale in the South China Sea and are fundamental to understanding the morphological, behavioral, and ecological perspectives of this cetacean species.

First visual sightings and echolocation signal recordings of Blainville's beaked whales ( Mesoplodon densirostris ) in the northern South China Sea - Lijun Dong; Wenzhi Lin; Mingming Liu; Binshuai Liu; Shenglan Chen; Mingli Lin; Yixi Shi; Songhai Li (Marine Mammal Science, 2025)

Survival and population size of the Indo‐Pacific humpback dolphins off the eastern Leizhou Peninsula - Wenzhi Lin; Shenglan Chen; Binshuai Liu; Ruiqiang Zheng; Agathe Serres; Mingli Lin; Mingming Liu; Songhai Li (Marine Mammal Science, 2025)
Indo‐Pacific humpback dolphins form a resident population off the east coast of Leizhou Peninsula (LZP) in South China. The most recent study suggested ~1,500 individuals in this area, making this population one of only two populations of this species exceeding 1,000 individuals. However, demographic information regarding this population has been lacking since 2012. Using a 5‐year (2019–2023) photo‐identification data set, we examined two key demographic parameters of the LZP population, namely the apparent survival and population size, using multistate capture‐recapture analyses. Annual survival probabilities (φ) changed over time, fluctuating between 0.942 and 0.961 for adults, and between 0.787 and 0.837 for juveniles. Jolly‐Seber multistate model analyses resulted in highly comparable noncalf population size estimates from 2020 to 2023 ( 2020 = 479, SE = 28; 2021 = 458, SE = 29; 2022 = 481, SE = 27; 2023 = 446, SE = 31). By reviewing the available demographic information, we conclude that the population size of LZP humpback dolphins has been previously overestimated. The time‐dependent survivals seemingly reflect a dynamic development of anthropogenic disturbance during the pandemic period. We propose that the population status should be re‐evaluated, especially in the postpandemic era when the human activities came back to “normal” levels.

Echolocation signals recorded in the presence of Deraniyagala's beaked whales ( Mesoplodon hotaula ) in the western Pacific (South China Sea) indicate species‐specificity and intraspecific variation - Lijun Dong; Yuhang Song; Wenzhi Lin; Mingming Liu; Mingli Lin; Songhai Li (Marine Mammal Science, 2025)
Deraniyagala's beaked whale ( Mesoplodon hotaula ) is one of the least‐known beaked whale species, with only a few of possible live sightings being documented to date. Here, vocalizations of Deraniyagala's beaked whales were recorded using drifting recording systems in the confirmed presence of this whale in the northern South China Sea (SCS) in 2021. A total of 699 qualified frequency‐modulated (FM) pulses were used to calculate frequency and duration measurements. FM pulses had a median peak frequency of 43.3 kHz and median interpulse interval (IPI) of 244.6 ms. Both the spectra measurements and clustering analysis showed the recorded clicks closely resemble the clicks of beaked whales at Palmyra Atoll (presumed to belong to Deraniyagala's beaked whale). Compared with other Ziphiidae species, interspecific differences were also observed. Distinguishing between Deraniyagala's and ginkgo‐toothed ( M. ginkgodens ) beaked whales with acoustic data sets seems to prove feasible. Our results also suggested that Deraniyagala's beaked whales may produce more than one subtype of FM pulses. This study presents the first description of echolocation clicks produced by this species based on the confirmed visual sightings. It is beneficial to identify the species in passive acoustic monitoring records and gain further insight into this species' vocalizations.

Observations on Deraniyagala's beaked whale ( Mesoplodon hotaula ) in the South China Sea based on the first confirmed live sightings - Mingming Liu; Wenzhi Lin; Binshuai Liu; Shenglan Chen; Mingli Lin; Lijun Dong; Hui Kang; Mingyue Ouyang; Zixin Yang; Xiaoyu Huang; Massimiliano Rosso; L. Todd Pusser; et al. (Marine Mammal Science, 2025)
Deraniyagala's beaked whale, Mesoplodon hotaula , was previously known from eight published strandings and no confirmed live sightings, making it one of the least‐known cetaceans. We conducted six cetacean survey cruises in the South China Sea between 2019 and 2023, and during 120 sea‐days we recorded 12 sightings of unidentified Mesoplodon . From biopsy samples and acoustic recordings, five sightings were subsequently confirmed as M. hotaula. Using photographs, we provide the first field descriptions and observations of this species. The calf/juvenile has a distinctive facial coloration and dorsal striping pattern that appear to be diagnostic among Indo‐Pacific Mesoplodon ; among adult males, the dark rostrum of M. hotaula and the distinctively white‐tipped beak of ginkgo‐toothed beaked whale, M. ginkgodens , distinguish these similar‐looking, partially sympatric species. Mean group size was small (3.0, n = 5), with a preference for deep (2,156 m, n = 5), warm (30.3°C, n = 3) water. We update the known distribution of this species, present evidence of fishery interactions, and document the first reported mixed‐species Mesoplodon group: a juvenile Blainville's beaked whale M. densirostris associated with four M. hotaula. These sightings identify the South China Sea as a potentially important area for this almost completely unknown species.

Copper Homeostasis and Its Impact on Innate Immunity in Crustaceans - Hejia Chen; Xi Huang; Muhammad Tayyab; Mingming Zhao; Defu Yao; Zhihong Zheng; Xianliang Zhao; Yongzhen Zhao; Xiuli Chen; Bobo Zhang; Qiongqiong Yang; Yueling Zhang; et al. (Reviews in Aquaculture, 2025)
Copper, an essential micronutrient in crustaceans, plays vital roles in enzymatic processes, oxygen transport, pigmentation, and structural protein synthesis, including collagen and elastin. Recent research has elucidated its pivotal role in innate immunity of crustaceans, enhancing the immune response by promoting phagocytic activity, antimicrobial peptide production, and modulation of immune gene expression. Copper ions exhibit antimicrobial effects by disrupting cell membranes and inhibiting microbial proliferation. Furthermore, copper governs antioxidant defense mechanisms, protecting crustaceans against oxidative stress and infection. However, excessive copper can lead to toxicity, highlighting the need for strict maintenance of copper homeostasis. This review explores the complex processes of copper homeostasis in crustaceans, detailing transport mechanisms, storage proteins, and detoxification pathways. It emphasizes copper's critical physiological and immunological functions, contributing to a comprehensive understanding of its multifaceted roles in crustaceans and laying groundwork for further exploration of copper homeostasis as a strategy for boosting crustacean immunity. Aquaculture practices significantly influence copper levels in crustaceans. Effective copper management, including monitoring techniques, water treatment strategies, and regulatory frameworks, is crucial for both crustacean welfare and environmental sustainability.

Hidden deposit exploration using the tectono-geochemistry method in the western Xicheng ore field, China - Zhizhong Cheng; Qiang Wang; Junchen Liu; Zhenshan Pang; Tingjie Yan; Zezhong Du; Mingming Bing; Huixiang Yuan; Chenggui Lin (Journal of Geochemical Exploration, 2024)

Analysis of the phytoremediation potential, rice safety, and economic benefits of light to moderate Cd-contaminated farmland in oilseed rape-rice rotation with straw removal: A three-year field trial - Mingming Li; Lin Chen; Yang Yang; Shuangjun Wu; Qiuguo Zhang; Xiao Deng; Si Luo; Qingru Zeng (Environmental Research, 2024)

Probing the capacity of a spatiotemporal deep learning model for short-term PM2.5 forecasts in a coastal urban area - Qi Liao; Mingming Zhu; Lin Wu; Dawei Wang; Zixi Wang; Si Zhang; Wudi Cao; Xiaole Pan; Jie Li; Xiao Tang; Jinyuan Xin; Yele Sun; et al. (Science of The Total Environment, 2024)

Species diversity and critical habitats of offshore and deep-diving cetaceans in the South China Sea - Mingming Liu; Wenzhi Lin; Mingli Lin; Lijun Dong; Binshuai Liu; Shenglan Chen; Mingyue Ouyang; Peijun Zhang; Zixin Yang; Hui Kang; Songhai Li (Biological Conservation, 2024)

Sensitive and quick electrochemiluminescence biosensor for the detection of reactive oxygen species in seminal plasma based on the valence regulation of gold nanoclusters - Lingjun Cheng; Yuanyuan Yang; Shaobin Lin; Canping Su; Mingming You; Yating Liu; Qingfei He; Jiaming Chen; Zhenyu Lin; Guolin Hong (Analytica Chimica Acta, 2024)

Enhanced degradation of roxarsone and removal of total arsenic by zero-valent iron with ligand under aerobic condition - Menghua Cao; Jun Lin; Mingming Zheng; Shuxin Tu; Shuanglian Xiong; Dun Fang (Journal of Environmental Chemical Engineering, 2024)

Using local ecological knowledge to inform regional conservation prioritization for threatened marine megafauna - Mingli Lin; Mingming Liu; Heidi Ma; Samuel T. Turvey; Songhai Li (Ocean & Coastal Management, 2024)

The mucosal immunity in crustaceans: Inferences from other species - Ruixue Hao; Mingming Zhao; Muhammad Tayyab; Zhongyang Lin; Yueling Zhang (Fish & Shellfish Immunology, 2024)

Development of PEG-mediated genetic transformation and gene editing system of Bryum argenteum as an abiotic stress tolerance model plant - Fengjun Leng; Guiwei Zhou; Ruoyuan Shi; Chengyang Liu; Yirui Lin; Xinqiang Yu; Yanhua Zhang; Xiangxi He; Zhu Liu; Mingming Sun; Fang Bao; Yong Hu; et al. (Plant Cell Reports, 2024)

Deep convolutional neural networks for aged microplastics identification by Fourier transform infrared spectra classification - Ganning Zeng; Yuan Ma; Mingming Du; Tiansheng Chen; Liangyu Lin; Mengzheng Dai; Hongwei Luo; Lingling Hu; Qian Zhou; Xiangliang Pan (Science of The Total Environment, 2024)

Phosphorus-containing reactive compounds to prepare fire-resistant vinyl resin for composites: Effects of flame retardant structures on properties and mechanisms - Mingming Yu; Yuji Chu; Wang Xie; Lin Fang; Ousheng Zhang; Musu Ren; Jinliang Sun (Chemical Engineering Journal, 2024)

Short‐finned pilot whales in the South China Sea: Insights into regional distribution, movement pattern, and habitat characteristics - Mingming Liu; Wenzhi Lin; Mingli Lin; Lijun Dong; Songhai Li (Marine Mammal Science, 2024)
Little scientific knowledge is available for short‐finned pilot whales in the South China Sea (SCS). Here, we integrated historical records, ship‐based observation, and satellite‐tagging data to investigate ecological and behavioral characteristics of pilot whales in the SCS. Historical records since the 1990s showed the widespread spatial occurrence of pilot whales along the coastal SCS, suggesting that the species may inhabit this region. During our dedicated ship‐based surveys (2019–2022) in the SCS, 19 groups of pilot whales were encountered in Xisha‐Zhongsha waters, which supported the hypothesis inferred from historical data. We believe that Xisha‐Zhongsha waters are important habitats for pilot whales, demonstrated by the large group size ( M = 44.7 ± 42.4 SD individuals), the high proportion of recorded maternal groups (17/19), mixed‐species associations, and deep‐water habitat characteristics. During field surveys, we conducted satellite‐tagging experiments on two adult pilot whales, with tracking periods of 35 and 13 days, respectively. Satellite‐tracking data provided evidence of possible residency of the tagged whales, as both displayed overlapping ranges and nondirectional movement. This research provides preliminary baseline data on occurrence, distribution, movement, habitat use, and likely residency of pilot whales in the SCS, which can facilitate future research and conservation effort.

Penaeid shrimp counteract high ammonia stress by generating and using functional peptides from hemocyanin, such as HMCs27 - Mingming Zhao; Zhihong Zheng; Chuanqi Wang; Defu Yao; Zhongyang Lin; Yongzhen Zhao; Xiuli Chen; Shengkang Li; Jude Juventus Aweya; Yueling Zhang (Science of The Total Environment, 2023)

Recovery of valuable elements from solid waste with the aid of external electric field: A review - Yusufujiang Mubula; Mingming Yu; Delong Yang; Bo Lin; Yuting Guo; Tingsheng Qiu (Journal of Environmental Chemical Engineering, 2023)

A shared role of the myocardin-family transcriptional coactivators in cardiomyocyte maturation - Yuxuan Guo; Yangpo Cao; Blake D. Jardin; Neil Mazumdar; Congting Guo; Luzi Yang; Junsen Lin; Zhan Chen; Qing Ma; Mingming Zhao; Erdan Dong; William T. Pu (Science China Life Sciences, 2023)

Effects of abnormal expression of CD73 on malignant phenotype of nasopharyngeal carcinoma - Bin Jiang; Mingming Tang; Si Shi; Haijing Xie; Si Pan; Lin Zhang; Juping Sheng (Journal of Molecular Histology, 2023)

Life History Parameters to Inform Pattern of Prenatal Investment in Marine Mammals - Xiaoyu Huang; Mingming Liu; Samuel T. Turvey; Mingli Lin; Songhai Li (Journal of Marine Science and Engineering, 2023)
Marine mammals are a diverse group of aquatic animals that exhibit wide variation in body size, living conditions, breeding habitat, social behaviour and phylogeny. Although case studies about prenatal investment in cetaceans and pinnipeds have been investigated, comparative studies across different marine mammal taxonomic groups have not yet been conducted systematically. Here, six life history parameters from 75 marine mammal species were collected based on a meta-analysis of the existing literature, and prenatal investment patterns for different taxonomic groups were explored using an unsupervised artificial neural network of a self-organizing map (SOM). Most marine mammal species can be clearly divided into two clusters of small-bodied taxa (small-bodied toothed whales, pinnipeds) and large-bodied taxa (baleen whales, sperm whales and beaked whales, large-bodied toothed whales) based on their distribution within SOM feature maps. Gestation periods and breeding intervals are significantly shorter in pinnipeds than in small-bodied toothed dolphins despite being similar in body size, indicating their adaption to birthing and nursing on land or ice floes. Specific deep-dive feeding behaviour seems to have no impact on the prenatal investment of beaked whales and sperm whales, as these species exhibit a similar capital breeding strategy to baleen whales. Medium-bodied sirenians adopt an intermediate strategy between small-bodied and large-bodied toothed whales, suggesting their prenatal investment strategy is not affected by herbivorous habits. Overall, our results support the body-size hypothesis and breeding-substrate hypothesis and indicate that prenatal investment strategies of marine mammals are possibly not influenced by feeding habits or social behaviour. We suggest that effective conservation measures for small-bodied toothed whales and pinnipeds should prioritize the protection of habitats and minimize human disturbance, whereas conservation measures for large-bodied whales and beaked whales should focus on strategies to prevent substantial declines in population size.

Insight into the selective oxidation behavior of organic pollutants via Ni-N4-C mediated electron transfer pathway - Huchuan Yan; Cui Lai; Shiyu Liu; Dongbo Wang; Xuerong Zhou; Mingming Zhang; Ling Li; Dengsheng Ma; Fuhang Xu; Xiuqin Huo; Lin Tang; Ming Yan; et al. (Chemical Engineering Journal, 2023)

An interview-based investigation of marine megafauna bycatch in the northern South China Sea - Mingli Lin; Mingming Liu; Samuel T. Turvey; Songhai Li (Biological Conservation, 2023)

Injuries and skin condition of Indo‐Pacific humpback dolphins ( Sousa chinensis ) in the northern South China Sea - Agathe Serres; Wenzhi Lin; Binshuai Liu; Mingli Lin; Mingming Liu; Songhai Li (Marine Mammal Science, 2023)
Indo‐Pacific humpback dolphins ( Sousa chinensis ) inhabiting the Chinese coastline of the northern South China Sea are subject to intense human activity. To investigate potential impacts to dolphins, photographs taken from 2010 to 2021 in five different locations were analyzed. Among individual dolphins ( N = 1,159), 10.6% presented human‐induced injuries. Adults were more frequently injured than young dolphins, and individuals from around Jiangmen, Hainan, and Sanniang Bay presented the highest injury prevalence. More research should be conducted in areas that have been subject to less research, such as Jiangmen and Hainan, and the dolphin watching activities occurring in Sanniang Bay should be monitored and regulated. Forty‐seven percent of dolphins presented skin conditions, with orange patches being the most frequent (41.5%). Orange patches and hyper‐pigmented pink spots were significantly less prevalent in summer and fall than in winter and spring. Orange patches were less frequent in females than in males, as well as with calves relative to older age classes. Seasonal patterns may be linked to water temperatures, while demographic patterns may be associated with immune defenses. These findings allow for a better understanding of the potential impact of human activities on Indo‐Pacific humpback dolphins and should inform further conservation measures.

Tuning the intrinsic catalytic sites of magnetite to concurrently enhance the reduction of H2O2 and O2: Mechanism analysis and application potential evaluation - Ling Li; Min Cheng; Eydhah Almatrafi; Lei Qin; Shiyu Liu; Huan Yi; Lu Yang; Zhexin Chen; Dengsheng Ma; Mingming Zhang; Xuerong Zhou; Fuhang Xu; et al. (Journal of Hazardous Materials, 2023)

Promoting mechanism of CuO on catalytic performance of CeFe catalyst for simultaneous removal of NO and CO - Xiaodi Li; Shan Ren; Zhichao Chen; Lin Chen; Mingming Wang; Liang Wang; Anping Wang (Fuel, 2023)

A Self-attention Graph Convolutional Network for Precision Multi-tumor Early Diagnostics with DNA Methylation Data - Xue Jiang; Zhiqi Li; Aamir Mehmood; Heng Wang; Qiankun Wang; Yanyi Chu; Xueying Mao; Jing Zhao; Mingming Jiang; Bowen Zhao; Guanning Lin; Edwin Wang; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2023)

An interlayer flame retardant method to effectively fire retardant and reinforce CF/EP composites by nanofiber film intercalation - Mingming Yu; Yuji Chu; Wang Xie; Lin Fang; Xueqiang Liu; Ousheng Zhang; Musu Ren; Jinliang Sun (Chemical Engineering Journal, 2023)

Acoustic evidence of Cuvier's beaked whales ( Ziphius cavirostris ) in the northern South China Sea - Lijun Dong; Mingming Liu; Wenzhi Lin; Mingli Lin; Zixin Yang; Songhai Li (Marine Mammal Science, 2023)

Design of a highly efficient Cu-based catalyst with two functional areas: The role of Cu0 and oxygen vacancies in Fenton-like system - Cui Lai; Lu Yang; Ling Li; Dengsheng Ma; Min Cheng; Shiyu Liu; Mingming Zhang; Huchuan Yan; Chensi Tang; Zhexin Chen; Lin Tang (Chemical Engineering Journal, 2023)

Most root-derived carbon inputs do not contribute to long-term global soil carbon storage - Guocheng Wang; Liujun Xiao; Ziqi Lin; Qing Zhang; Xiaowei Guo; Annette Cowie; Shuai Zhang; Mingming Wang; Songchao Chen; Ganlin Zhang; Zhou Shi; Wenjuan Sun; et al. (Science China Earth Sciences, 2023)

Season, age, sex, and location impact the density of tooth rake mark and dorsal fin notch of Indo‐Pacific humpback dolphins ( Sousa chinensis ) in the northern South China Sea - Agathe Serres; Wenzhi Lin; Binshuai Liu; Mingli Lin; Mingming Liu; Shenglan Chen; Songhai Li (Marine Mammal Science, 2023)
Tooth rake marks are usually used as an indicator of received aggression in odontocetes whose social interactions are difficult to observe directly. Photographic data from five locations of the northern South China Sea were used to analyze seasonal, demographic, and geographic effects on the density of tooth rake marks and dorsal fin notches in Indo‐Pacific humpback dolphins ( Sousa chinensis , IPHDs). The analysis revealed that fresh tooth rake marks were most frequent during the dry season. Males exhibited significantly higher rake mark density than females and rake density declined significantly with age. The density of notches was also significantly higher for males than for females, and lower for young dolphins than for mid‐aged and adult ones. Geographically, tooth rake mark and notch density were the highest in Sanniang Bay and Southwestern Hainan. These results provide indirect evidence of variation in social interactions across seasons, across the lifespan of an individual, between sexes, and among different locations. This variation may result from changes in biological parameters, differences in social lives, and habitat characteristics. A model to determine the sex of dolphins was tested, and after further validation, such sex assignment could contribute to understanding IPHDs' social structure.

Ranging pattern development of a declining delphinid population: A potential cascade effect of vessel activities - Wenzhi Lin; Ruiqiang Zheng; Binshuai Liu; Shenglan Chen; Mingli Lin; Agathe Serres; Mingming Liu; Wenhua Liu; Songhai Li (Journal of Environmental Management, 2023)

Unveiling the inductive strategy of different precipitants on MnFeO catalyst for low-temperature NH3-SCR reaction - Zhichao Chen; Shan Ren; Xiangdong Xing; Xiaodi Li; Lin Chen; Mingming Wang (Fuel, 2023)

Phenyl-imidazole based and nitrogen rich hyper-crosslinked polymer for sensitive determination of aflatoxins - Mingming Xu; Zhijun Zhou; Lin Hao; Zhi Li; Jie Li; Qianqian Wang; Weihua Liu; Chun Wang; Zhi Wang; Qiuhua Wu (Food Chemistry, 2023)

Chromosome-Level Genome Assembly of the Rough-Toothed Dolphin (Steno bredanensis) - Haiyu Gao; Hui Kang; Yaolei Zhang; Jiahao Wang; Wenzhi Lin; Peijun Zhang; Mingli Lin; Mingming Liu; Guangyi Fan; Songhai Li (Journal of Marine Science and Engineering, 2023)
The rough-toothed dolphin (Steno bredanensis), the single extant species of the genus Steno, inhabits tropical and subtropical oceans. It is an attractive species for studying aquatic adaptation and evolution. The latest advances in high-throughput sequencing are transforming the study of marine mammals and contributing to understanding various phenomena at the species and population level by determining high-quality genomes. Here, to comprehensively understand the genetic features and explore the molecular basis of aquatic adaption, the chromosome-level genome assembly and comparative genomics analyses of S. bredanensis were performed. The 2.30 Gb final genome assembly of S. bredanensis (scaffold N50 length of 105.53 Mb) was obtained using single-tube long fragment read (stLFR) and Hi-C technologies. The genome assembly clearly revealed the preservation of large chromosomal fragments between S. bredanensis and the melon-headed whale (Peponocephala electra). The S. bredanensis genome contained 19,451 predicted protein-coding genes, of which about 92.33% have functional annotations. The genome assembly and gene sets showed high completeness, with a BUSCO score of 90.6% and 97.3%, respectively. We also identified several positively selected genes specific to S. bredanensis, which may be related to fat cell differentiation, tooth morphogenesis, and immunoregulatory activity. Finally, the demographic dynamics of S. bredanensis were estimated by the pairwise sequentially Markovian coalescent (PSMC) model and found that the population was affected by the climate at the time. We demonstrated that improved continuity and accuracy of the assembled sequence warranted the adoption of this chromosome-level genome as the reference genome and advanced the understanding of genetic features of the rough-toothed dolphin, which will be essential for future evolutionary studies and the protection of this species.

Anomalous Coloration of Indo-Pacific Humpback Dolphins off Southern China - Wenzhi Lin; Shenglan Chen; Ruiqiang Zheng; Agathe Serres; Binshuai Liu; Mingli Lin; Mingming Liu; Songhai Li (Journal of Marine Science and Engineering, 2023)
The Indo-Pacific humpback dolphin is characterized by a particular ontogenic change in body color from dark gray at birth to pure white (or with a few dark-gray spots) after reaching adulthood. Here, we report a spectrum of anomalous body color patterns observed on Indo-Pacific humpback dolphins off southern China. The occurrence of hypopigmentation and hyperpigmentation was described and compared among six putative dolphin populations. Low rates of anomalies in body color patterns were observed (

Assessment of cancer-related signaling pathways in responses to polystyrene nanoplastics via a kidney-testis microfluidic platform (KTP) - Mingming Xiao; Xinran Li; Xinlian Zhang; Xiaoxiao Duan; Houwei Lin; Sixiu Liu; Guodong Sui (Science of The Total Environment, 2023)

Floating macro-litter pollution in the northern South China Sea - Mingming Liu; Mingli Lin; Xiaoyu Huang; Zixin Yang; Francesco Caruso; Matteo Baini; Alessandro Bocconcelli; Massimiliano Rosso; Songhai Li (Environmental Pollution, 2023)

An S-scheme CdS/K2Ta2O6 heterojunction photocatalyst for production of H2O2 from water and air - Cui Lai; Mengyi Xu; Fuhang Xu; Bisheng Li; Dengsheng Ma; Yixia Li; Ling Li; Mingming Zhang; Danlian Huang; Lin Tang; Shiyu Liu; Huchuan Yan; et al. (Chemical Engineering Journal, 2023)

A peptide Epitope − Synthetic hydrogel polymer conjugate that mimics insecticidal protein Receptors. Application in environmental and biological analysis - Zihao Wan; Yalu Chen; Senhua Hu; Qiaolian Chen; Yuxin Li; Xiuhua Chen; Wenfeng Tan; Yongjun Lin; Kenneth J. Shea; Mingming Liu (Chemical Engineering Journal, 2023)

Target controlled alternative hybridization chain reaction for fluorescent detection of dual mycotoxins - Qin Ma; Yiyan Lin; Yun Yang; Wenming Yang; Wen Yun; Mingming Zhang; Lizhu Yang (Analytica Chimica Acta, 2023)

First Suction Cup Tagging on a Small and Coastal Form Bryde’s Whale (Balaenoptera edeni edeni) in China to Investigate Its Dive Profiles and Foraging Behaviours - Lijun Dong; Mingming Liu; Wenzhi Lin; Songhai Li (Journal of Marine Science and Engineering, 2022)
Small-and-coastal-form Bryde’s whales (Balaenoptera edeni edeni) are known to inhabit coastal and continental shelf waters. However, little is known on their ethological activities, especially underwater behaviours. Here, we deployed a suction cup tag on a small-and-coastal-form Bryde’s whale to study its ethological activities in Dapeng Bay, a coastal water of Shenzhen off the east Pearl River Estuary, China. The whale was tagged for 6 hours in total and displayed a head-lifting feeding behaviour 77 times during two tag deployments. The swim speed, dive duration and depth and bottom duration were collected by the tag to describe detailed information on dive profiles. The rate of feeding behaviours was observed decreasing with the presence of anthropogenic whale-approaching (AWA) boat activities occurring close (within 300 m) to the animal. Our study, for the first time, investigated behaviours of Bryde’s whales using suction cup tagging in Chinese waters. The results reveal the dive and feeding patterns of a small-and-coastal-form Bryde’s whale with short-term monitoring and provide a fundamental advancement in the knowledge of both the diving behaviour and the behavioural response of this subspecies to human activities. The findings are valuable for possible rescue of the investigated whale and for policy and management regarding conservation of this subspecies as well.

Marine heatwaves threaten key foraging grounds of sea turtles in Southeast Asian Seas - Aikaterini Konsta; Anastasia Chatzimentor; Mingli Lin; Charalmpos Dimitriadis; Amalia Kyprioti; Mingming Liu; Songhai Li; Aggeliki Doxa; Antonios D. Mazaris (Regional Environmental Change, 2022)

Evidence of interactions between sharks and Indo‐Pacific humpback dolphins ( Sousa chinensis ) in the northern South China Sea - Agathe Serres; Wenzhi Lin; Eric E. G. Clua; Mingli Lin; Mingming Liu; Songhai Li (Marine Mammal Science, 2022)

Low Survivals and Rapid Demographic Decline of a Threatened Estuarine Delphinid - Wenzhi Lin; Ruiqiang Zheng; Binshuai Liu; Shenglan Chen; Mingli Lin; Mingming Liu; Wenhua Liu; Songhai Li (Frontiers in Marine Science, 2022)
Beibu Gulf’s (BBG) Indo-Pacific humpback dolphins present both a genetic differentiation and phenotypical differences from conspecifics from other areas of the South China Sea. Given the recent urbanization and industrialization in southern China, humpback dolphins from the BBG warrant conservation attention. However, this population’s demographic trend is unclear, making it hard to take conservation measures. To assess the population status of humpback dolphins in the BBG, photo-identification surveys were conducted between 2015 and 2019 in the inshore region surrounding the Dafeng River Estuary, which represents the most urbanized and industrialized coastal area of the BBG region. Robust design modeling suggested a constant survival for the female adults (0.89, 95% CI: 0.83–0.94). In comparison, the survival of the juvenile and sex-undetermined adults dropped from 0.92 (95% CI: 0.75–0.98) in 2015 to 0.86 (95% CI: 0.71–0.94) in 2016 and bounced back to 0.89 (95% CI: 0.80–0.94) in 2018. The low level of survival may justify the rapid decline in the annual population size from 156 (95% CI: 133–184) in 2015 to 102 (95% CI: 98–107) in 2019. We found little impact of emigration on the dolphin demographic process. Instead, the low and fluctuating survivals, although with overlapping confidence intervals, seemingly suggested a presence of strong marine stressor(s). Our study highlighted that obtaining high-resolution data is essential to improving our understanding of the demographic dynamics. Moreover, the anthropogenic stress in the BBG region should be quantitatively studied in both temporal and spatial perspectives, to help depict the ecological response of the dolphins to anthropogenic activities.

Evolutionary and ecological patterns of scatter‐ and larder‐hoarding behaviours in rodents - Yongjun Zhang; Fei Yu; Xianfeng Yi; Weiwei Zhou; Rui Liu; Marcel Holyoak; Lin Cao; Mingming Zhang; Jiani Chen; Zhibin Zhang; Chuan Yan (Ecology Letters, 2022)
Scatter‐ and larder hoarding are the primary strategies of food‐hoarding animals and have important implications for plant‐animal interactions and plant recruitment. However, their origins and influencing factors have not been fully investigated across a wide range of taxa. Our systematic literature search amassed data for 183 seed‐hoarding rodent species worldwide and tested relationships of seed‐hoarding behaviours with phylogenetic signal, functional traits and environmental factors. We found that the evolution of hoarding strategies was not random in phylogeny, and scatter hoarding originated independently multiple times from larder hoarding. Rodents with higher encephalisation quotient (relative brain size), omnivorous diet (related to dependence on seeds) and inhabiting lower latitudes were disproportionately likely to scatter hoard. Despite body mass’s potential relationship with competition through food defence, it was associated with food‐hoarding strategy only in a few families. Our results show the need to study the community and ecological context of food‐hoarding behaviours.

Whistle characteristics of a newly recorded Indo‐Pacific humpback dolphin ( Sousa chinensis ) population in waters southwest of Hainan Island, China, differ from other humpback dolphin populations - Lijun Dong; Francesco Caruso; Jianchen Dong; Mingming Liu; Mingli Lin; Songhai Li (Marine Mammal Science, 2021)
Indo‐Pacific humpback dolphins ( Sousa chinensis ) use whistles to communicate with their conspecifics. Little is known about the acoustic repertoire of Indo‐Pacific humpback dolphins in waters southwest of Hainan Island, a newly recorded population in 2014. In this study, whistles of Hainan humpback dolphin population were collected by using autonomous acoustic recorders. The fundamental frequencies and durations of whistles were in ranges of 0.71–21.35 kHz and 0.06–2.22 s, respectively. Significant intraspecific differences in duration and frequency of whistles were found between the Hainan population and the other geographically neighboring populations (in Chinese waters) or the population in Malaysia waters. Compared with other Sousa species, significant interspecific differences were also observed. Based on clustering analysis, the whistle parameters of neighboring populations were likely similar to each other. Significant differences were found between humpback dolphins in waters southwest of Hainan Island and those dolphins in the neighboring areas, supporting the hypothesis that this population may be independent. Ambient noise measurements in waters of Hainan Island, Zhanjiang, and Sanniang Bay showed that humpback dolphin populations may use whistles with longer duration, lower frequency, and fewer inflection points for more effective communication to adapt to a noisier environment.

Group Size of Indo-Pacific Humpback Dolphins (Sousa chinensis): An Examination of Methodological and Biogeographical Variances - Mingming Liu; Mingli Lin; Xiaoming Tang; Lijun Dong; Peijun Zhang; David Lusseau; Songhai Li (Frontiers in Marine Science, 2021)
Observer-based counts and photo-identification are two well-established methods with an extensive use in cetacean studies. Using these two methods, group size has been widely reported, especially for small dolphins. Both methods may come with potential errors in estimating the group size, yet there is still a lack of comparison between both methods over a broad range of group size. Particularly, biogeographical variances in group size estimates were often mixed with methodological variances, making it difficult to compare estimates from different geographic regions. Here, group size estimates of a small, shallow-water, and near-shore delphinid species, Indo-Pacific humpback dolphins ( Sousa chinensis ), were simultaneously sampled using observer-based counts and photo-identification at three regions in the northern South China Sea. Data showed that dolphin group size from two methods were highly variable and associated with sampling regions. Generalized linear mixed models (GLMMs) indicated that dolphin group size significantly differed among regions. Statistical examinations further demonstrated dolphin group size could be affected by a complex combination of methodological and biogeographical variances. A common hurdle to examine potential factors influencing the estimation process is the inability to know the true group size at each sample. Therefore, other methods that could generate comparable estimates to represent true group size are warranted in future studies. To conclude, our findings present a better understanding of methodological and biogeographical variances in group size estimates of humpback dolphins, and help yield more robust abundance and density estimation for these vulnerable animals.

Combination of optimized tissue engineering bone implantation with heel-strike like mechanical loading to repair segmental bone defect in New Zealand rabbits - Cong Zhu; Jianbiao Lin; Huixiang Jiang; Jianting Gao; Mingming Gao; Benwen Wu; Weibin Lin; Guofeng Huang; Zhenqi Ding (Cell and Tissue Research, 2021)

The First Attempt of Satellite Tracking on Occurrence and Migration of Bryde’s Whale (Balaenoptera edeni) in the Beibu Gulf - Mingming Liu; Wenzhi Lin; Mingli Lin; Binshuai Liu; Lijun Dong; Peijun Zhang; Zixin Yang; Kexiong Wang; Liang Dai; Songhai Li (Journal of Marine Science and Engineering, 2021)
Satellite-tagging is increasingly becoming a powerful biotelemetry approach to obtain remote measurement through tracking free-living cetaceans, which can fill knowledge gaps on cetaceans and facilitate conservation management. Here, we made a first biologging attempt on baleen whales in Chinese waters. An adult Bryde’s whale in the Beibu Gulf was tagged to investigate potential occurrence areas and migration routes of this poorly studied species. The whale was satellite-tracked for ~6 days with 71 filtered Argos satellite locations, resulting in a linear movement distance of 464 km. At each satellite-tracking location, the water depth was measured as 42.1 ± 24.8 m on average. During the satellite-tracking period, the whale’s moving speed was estimated at 5.33 ± 4.01 km/h. These findings expanded the known distribution areas of Bryde’s whales in the Beibu Gulf and provided an important scientific basis for the regional protection of this species. We suggest that fine-scale movements, habitat use, and migratory behavior of Bryde’s whales in the Beibu Gulf need more biotelemetry research, using long-term satellite-tracking tags and involving enough individuals. Furthermore, the genetic relationship and possible connectivity of Bryde’s whales in the Beibu Gulf and adjacent waters should be examined.

Intra-Population Variability in Group Size of Indo-Pacific Humpback Dolphins (Sousa chinensis) - Mingming Liu; Mingli Lin; David Lusseau; Songhai Li (Frontiers in Marine Science, 2021)
Group size is a key social trait influencing population dynamics of group-living animals. The Indo-Pacific humpback dolphins (IPHDs), Sousa chinensis , a shallow water delphinid species, display a fission-fusion social system. Yet little is known about how social organization of this species vary with temporal scales and behavioral state. In this study, we sampled group size estimates from the world’s second largest population of humpback dolphins ( Sousa spp.), which inhabit the eastern waters of Zhanjiang, China. IPHD group sizes changed seasonally and inter-annually, but not with tidal phases. Group sizes also changed with behavioral state of IPHD groups and with number of mother-calf pairs present. IPHDs formed larger groups in the autumn than in other seasons, which might be related to seasonal changes in food availability and reproductive cycle. Of the groups observed, we recorded the presence of mother-calf pair in 85 groups (i.e., nursery groups: 47 ones with one pair, 25 ones with two pairs, and others with three pairs). Notably, nursery groups were about 2–4 times larger than non-nursery groups. In addition, group sizes greatly increased with the number of mother-calf pairs. Living in relatively large groups, more protection, food, and resources might be available for IPHD mothers and calves, and such social strategy provide higher reproduction efficiency and survival success for this species. During our observations, feeding (45.5%) and traveling (25.2%) represented the majority of IPHD’s behavioral budget, while socializing (8.4%) and resting/milling (6.8%) were not frequently observed. Resting/milling groups were approximately 50% smaller than feeding, traveling, or socializing groups, while the latter three types had a similar mean group size. Large groups when IPHDs foraged, traveled, or socialized, might provide more added group benefits. For the first time, our findings clearly revealed intra-population variability in IPHD group sizes across different behavioral and temporal variables, and provided a better understanding of IPHDs’ adaptations to various biological processes and ecological constraints.

Serum macrophage migration inhibitory factor as a potential biomarker to evaluate therapeutic response in patients with allergic asthma: an exploratory study - Huiyuan Zhu; Shaochun Yan; Jingshuo Wu; Zhong Zhang; Xiaolin Li; Zheng Liu; Xing Ma; Lina Zhou; Lin Zhang; Mingming Feng; Yiwei Geng; Aixin Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2021)

Deep Learning for Air Quality Forecasts: a Review - Qi Liao; Mingming Zhu; Lin Wu; Xiaole Pan; Xiao Tang; Zifa Wang (Current Pollution Reports, 2020)

Morphological and physiological variations of Cyclocarya paliurus under different soil water capacities - Ying Feng; Xiulian Lin; Lianwen Qian; Nengjing Hu; Chunfeng Kuang; Xiaofeng Li; Zheng Li; Liangrui Huang; Mingming Liu (Physiology and Molecular Biology of Plants, 2020)

Urban residential land expansion and agglomeration in China: a spatial analysis approach - Xiaofeng Zhao; Mingming Zhang; Ying Li; Xianjin Huang; Baiyuan Wang; Lin Zhang (Environment, Development and Sustainability, 2020)

Monitoring of a Nearshore Small Dolphin Species Using Passive Acoustic Platforms and Supervised Machine Learning Techniques - Francesco Caruso; Lijun Dong; Mingli Lin; Mingming Liu; Zining Gong; Wanxue Xu; Giuseppe Alonge; Songhai Li (Frontiers in Marine Science, 2020)

Simulating and assessing the evolution of collapsing gullies based on cellular automata-Markov and landscape pattern metrics: a case study in Southern China - Xiang Ji; Anita Thompson; Jinshi Lin; Fangshi Jiang; Shaoxin Li; Mingming Yu; Yanhe Huang (Journal of Soils and Sediments, 2019)

Spatial and vertical variations in the soil organic carbon concentration and its controlling factors in boreal wetlands in the Greater Khingan Mountains, China - Weidong Man; Dehua Mao; Zongming Wang; Lin Li; Mingyue Liu; Mingming Jia; Chunying Ren; Igor Ogashawara (Journal of Soils and Sediments, 2019)

Impacts of Land Cover Changes on Ecosystem Carbon Stocks Over the Transboundary Tumen River Basin in Northeast Asia - Hengxing Xiang; Mingming Jia; Zongming Wang; Lin Li; Dehua Mao; Da Zhang; Guishan Cui; Weihong Zhu (Chinese Geographical Science, 2018)

Remote Monitoring of Expansion of Aquaculture Ponds Along Coastal Region of the Yellow River Delta from 1983 to 2015 - Chunying Ren; Zongming Wang; Bai Zhang; Lin Li; Lin Chen; Kaishan Song; Mingming Jia (Chinese Geographical Science, 2018)

Assessing the conservation effectiveness of wetland protected areas in Northeast China - Chunyan Lu; Zongming Wang; Lin Li; Puzhou Wu; Dehua Mao; Mingming Jia; Zhangyu Dong (Wetlands Ecology and Management, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Notch3/Akt signaling contributes to OSM-induced protection against cardiac ischemia/reperfusion injury - Mingming Zhang; Chen Wang; Jianqiang Hu; Jie Lin; Zhijing Zhao; Min Shen; Haokao Gao; Na Li; Min Liu; Pengfei Zheng; Cuiting Qiu; Erhe Gao; et al. (Apoptosis, 2015)

Myo10 is required for neurogenic cell adhesion and migration - Huali Yu; Mingming Lai; Yuguang Guo; Lin Yuan; Yongsheng Lan; Xingzhi Wang; Xiaojuan Zhu (In Vitro Cellular & Developmental Biology - Animal, 2015)

Characterization of fly ash from a circulating fluidized bed incinerator of municipal solid waste - Lin Zhang; Xiaowen Su; Zhixuan Zhang; Siming Liu; Yuxin Xiao; Mingming Sun; Jixin Su (Environmental Science and Pollution Research, 2014)

Mapping Wetland Areas Using Landsat-Derived NDVI and LSWI: A Case Study of West Songnen Plain, Northeast China - Zhangyu Dong; Zongming Wang; Dianwei Liu; Kaishan Song; Lin Li; Mingming Jia; Zhi Ding (Journal of the Indian Society of Remote Sensing, 2014)

Mapping China’s mangroves based on an object-oriented classification of Landsat imagery - Mingming Jia; Zongming Wang; Lin Li; Kaishan Song; Chunying Ren; Bo Liu; Dehua Mao (Wetlands, 2014)

Effects of Sugarcane Ratooning Cultivation on the Alteration of Bacterial Communities in the Rhizosphere Soil - Lin Sheng; Zhang Aijia; Wang Rongyu; Cheng Ting; Zhou Mingming; Yuan Zhaonian; Lin Wenxiong (Sugar Tech, 2012)

Evaluation of Docetaxel-Loaded Intravenous Lipid Emulsion: Pharmacokinetics, Tissue Distribution, Antitumor Activity, Safety and Toxicity - Mingming Zhao; Min Su; Xia Lin; Yanfei Luo; Haibing He; Cuifang Cai; Xing Tang (Pharmaceutical Research, 2010)

Preliminary validation of high performance liquid chromatography method for detection of methyl-testosterone residue in carp muscle - Jie Jiang; Hong Lin; Xiaoting Fu; Mingming Li (Journal of Ocean University of China, 2005)